Fibroblast Activation Protein-α and the Immune Landscape: Unraveling T1 Non–muscle-invasive Bladder Cancer Progression - Tim Muilwijk; Loïc Baekelandt; Murat Akand; Sofie Daelemans; Koen Marien; Yannick Waumans; Pieter-Jan van Dam; Mark Kockx; Thomas Van den Broeck; Ben Van Cleynenbreugel; Frank Van der Aa; Thomas Gevaert; et al. (European Urology Open Science, 2024)
Background and objective: The tumor microenvironment (TME) in non–muscle-invasive bladder cancer (NMIBC) plays an important role in the anticancer response. We aimed to identify the prognostic biomarkers in the TME of patients with NMIBC for progression to ≥T2. Methods: From our institutional database, 40 patients with T1 high-risk NMIBC who progressed were pair matched for Club Urologico Español de Tratamiento Oncologico (CUETO) progression variables with 80 patients who never progressed despite longer follow-up. Progression was defined as ≥T2 or extravesical disease. Patients were treated at least with bacillus Calmette-Guérin (BCG) induction (five or more of six doses). Immunohistochemical (IHC) markers for the TME were used on tissue at first T1 diagnosis: CD8-PanCK, GZMB-CD8-FOXP3, CD163, PD-L1 SP142/SP263, fibroblast activation protein-α (FAP), and CK5-GATA3. Full tissue slides were annotated digitally. Relative marker area (IHC-positive area/total area) or density (IHC-positive cells per area; n/mm2) was calculated, differentiating between regions of interest (ROIs; T1, Ta, and carcinoma in situ) and between compartments (stromal, epithelial, and combined). Differences in IHC variables were assessed using the t test, for continuous variables using analysis of variance and comparisons of more than two groups using Tukey’s test. Conditional logistic regression for progression at 5-yr follow-up was performed with clusters based on pair matching. Key findings and limitations: Only FAP expression (increase per 50%) in T1 (odds ratio [OR]: 1.33; 95% confidence interval [CI]: 1.04–1.70) and all ROIs combined (OR: 1.62; 95% CI: 1.14–2.29) correlated significantly with progression. None of the other clinicopathological/IHC variables correlated with progression. Conclusions and clinical implications: FAP is a potential prognostic biomarker for progression in high-risk NMIBC. FAP is a marker for cancer-associated fibroblasts and is linked to immunosuppression and neoangiogenesis, which makes future investigation clinically relevant. Patient summary: We found that progression of high-risk non–muscle-invasive bladder cancer to muscle-invasive disease is less in patients with lower fibroblast activation protein-α (FAP) expression, which is a marker for cancer-associated fibroblasts.